2022
DOI: 10.3389/fpsyg.2022.795951
|View full text |Cite
|
Sign up to set email alerts
|

Early Developmental Trajectories in Infants With Neurofibromatosis 1

Abstract: ObjectiveTo examine the trajectories of cognitive, motor and behavioural development in infants with NF1 compared to infants without a family history of neurodevelopmental difficulties.Study designInfants with NF1 and low-risk controls were recruited from 5 months of age and followed longitudinally. Data from standardised tests was gathered at 5, 10 and 14 months and developmental trajectories of motor, language, behaviour, sleep, social development and parent–infant interaction were examined. Linear mixed mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Consistent with a previous longitudinal study of NF1 children aged 21-40 months, 13 we largely found no sex differences in the trajectories of cognitive, behavioural or social development. These sex differences may emerge at a later timepoint, as there are significant sex differences observed in cross-sectional studies in school-age children with NF1.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with a previous longitudinal study of NF1 children aged 21-40 months, 13 we largely found no sex differences in the trajectories of cognitive, behavioural or social development. These sex differences may emerge at a later timepoint, as there are significant sex differences observed in cross-sectional studies in school-age children with NF1.…”
Section: Discussionsupporting
confidence: 92%
“…Previous papers from our group examined trajectories of cognitive and adaptive behavioural development in infants with NF1 aged 5 to 14 months compared with typically developing (TD) children. 13 At this early stage in development, no group differences were observed in trajectories of cognitive and adaptive functioning, nor differences on social communication measures. However, early differences in neural processing including auditory processing and excitation/inhibition balance were observed, both of which were related to later autistic traits.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations